PENAFSIRAN ULI AL-AMR PADA KITAB MARAH LABID KARYA NAWAWI AL-BANTANI - Khuluqi , Hasanal (QOF, 2020)
Imam Nawawi al-Bantani is one of the Indonesian scholars who was influential in the spread of Islam in the early 19th century. One of his thoughts on the interpretation of the concept of uli al-amr is contained in Marah Labid, according to Nawawi al-Bantani, it is forbidden to obey a leader who is wrong and not legally elected (a colonizer). The interpretation of Nawawi al-Bantani at one time certainly contradicts the interpretation of Islamic scholars in general, which requires further reading on all matters affecting its interpretation products. Uli al-amr is all scholars from among the ahlu al-halli wa al-'aqdi, true leaders and a just ruler. As long as the rules and orders do not conflict with the Qur'an, sunnah, ijma ’, and qiyas, obeying the uli al-amr command is a must.